Potential and limitations of satellite laser altimetry for monitoring water surface dynamics: ICESat for US lakes - Shu, Liu; Jiang, Qigang; Zhang, Xuesong; Zhao, Kaiguang (International Journal of Agricultural and Biological Engineering, 2017)
Elevation measurements from the Ice, Cloud and Land Elevation Satellite (ICESat) have been applied to monitor dynamics of lakes and other surface water bodies. Despite such potential, the true utility of ICEsat--more generally, satellite laser altimetry--for continuously tracking surface water dynamics over time has not been adequately assessed, especially in the continental or global contexts. This study analyzed elevation derived from ICESat data for the conterminous United States and examined the potential and limitations of satellite laser altimetry in monitoring the water level dynamics. Owing to a lack of spatially-explicit ground-based water-level data, the high-fidelity land elevation data acquired by airborne lidar were firstly resorted to quantify ICESat’s ranging accuracy. Trend and frequency analyses were then performed to evaluate how reliably ICESat could capture water-level dynamics over a range of temporal scales, as compared to in-situ gauge measurements. The analytical results showed that ICESat had a vertical ranging error of 0.16 m at the footprint level—an lower limit on the detectable range of water-level dynamics. The sparsity of data over time was identified as a major factor limiting the use of ICESat for water dynamics studies. Of all the US lakes, only 361 had reliable ICESat measurements for more than two flight passes. Even for those lakes with sufficient temporal coverage, ICESat failed to capture the true interannual water-level dynamics in 32% of the cases. Our frequency analysis suggested that even with a repeat cycle of two months, ICESat could capture only 60% of the variations in water-level dynamics for at most 34% of the US lakes. To capture 60% of the water-level variation for most of the US lakes, a weekly repeated cycle (e.g., less than 5 d) is needed – a requirement difficult to meet in current designs of spaceborne laser altimetry. Overall, the results highlight that current or near-future satellite laser missions, though with high ranging accuracies, are unlikely to fulfill the general needs in remotely monitoring water surface dynamics for lakes or reservoirs.Keywords: ICESat, lidar, water resources, lake dynamics, water level, satellite laser altimetry, lake surfaces, repeat cycleDOI: 10.25165/j.ijabe.20171005.3426Citation: Liu S, Jiang Q G, Zhang X S, Zhao K G. Potential and limitations of satellite laser altimetry for monitoring water surface dynamics: ICESat for US lakes. Int J Agric & Biol Eng, 2017; 10(5): 154–165.